2020
DOI: 10.1186/s12913-020-05139-z
|View full text |Cite
|
Sign up to set email alerts
|

Identifying no-harm incidents in home healthcare: a cohort study using trigger tool methodology

Abstract: Background: Patient safety in home healthcare is largely unexplored. No-harm incidents may give valuable information about risk areas and system failures as a source for proactive patient safety work. We hypothesized that it would be feasible to retrospectively identify no-harm incidents and thus aimed to explore the cumulative incidence, preventability, types, and potential contributing causes of no-harm incidents that affected adult patients admitted to home healthcare. Methods: A structured retrospective re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 37 publications
0
14
0
1
Order By: Relevance
“…Trigger tool-based methods have been adapted to many clinical contexts and translated to different languages. There are modified trigger tools for emergency department [17], surgery [18], paediatrics [19,20], geriatric patients [10], home healthcare [21,22], and for discovering medication errors [11]. GTT has been translated and modified to be used in different countries, for example Italy [23], Brazil [24], Portugal [25], China [10], Germany [18], Switzerland [9], Finland [26], Sweden [27], Norway [28] and Denmark [16].…”
Section: B) Use Of Trigger Tools In Different Settingsmentioning
confidence: 99%
“…Trigger tool-based methods have been adapted to many clinical contexts and translated to different languages. There are modified trigger tools for emergency department [17], surgery [18], paediatrics [19,20], geriatric patients [10], home healthcare [21,22], and for discovering medication errors [11]. GTT has been translated and modified to be used in different countries, for example Italy [23], Brazil [24], Portugal [25], China [10], Germany [18], Switzerland [9], Finland [26], Sweden [27], Norway [28] and Denmark [16].…”
Section: B) Use Of Trigger Tools In Different Settingsmentioning
confidence: 99%
“…Open access on safety in medication management and prevention of falls. [7][8][9][10][11] A large research gap remains on the broader safety perspective, encompassing the older person's behaviour and lifestyle, the social and physical home environment, and provision of both medical healthcare and social care, which have been identified as important domains of safety in home care. 4 12 13 A literature review on home care in European countries showed that there is limited information on how practical care models are related to outcomes such as safety in home care and that information about home care services is skewed, both within and across countries.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Detailed event presentation; sorted by column total. References [12,22,24,36,37] Informed Consent Statement: Informed consent was obtained from all subjects involved in the study.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Putting an additional focus on no-harm incidents provides valuable information on areas for improvement and learning from how to anticipate and reduce emerging risks before patient harm occurs. Investigating AEs and no-harm incidents is important to gain knowledge and understanding of how to improve patient safety [ 12 ]. Therefore, the information on no-harm incidents provides an additional perspective on patient safety during care services and the opportunity to improve areas at risk for patient harm [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation